2019
DOI: 10.1101/623124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivomicrostructural heterogeneity of white matter lesions in Alzheimer’s disease using tissue compositional analysis of diffusion MRI data

Abstract: White matter hyperintensities (WMH) are commonly observed in elderly individuals, and are typically more prevalent in Alzheimer's disease subjects than in healthy subjects. These lesions can be identified on fluid attenuated inversion recovery (FLAIR) MRI, on which they are hyperintense compared to their surroundings. These MRI-visible lesions appear homogeneously hyperintense despite known heterogeneity in their pathological underpinnings, and are commonly regarded as surrogate markers of small vessel disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Standard neuroimaging techniques do not provide quantifiable data on brain microstructural architecture, however this study has demonstrated a reproducible and reliable method for obtaining whole brain maps with quantifiable estimates of brain microstructure. This measure is stable enough to be used in longitudinal studies lasting at least up to three months; and provides information on a voxel-or region-wise basis for analysis of subcortical structures, lesions, or developing brains (Dhollander et al, 2017;Mito et al, 2018;Mito et al, 2019;Bastiani et al, 2019). Related microstructural analysis of free water signal fractions has been performed in the context of Parkinson's disease (Ofori et al, 2015;Burciu et al, 2016), Schizophrenia (Pasternak et al, 2012;Mandl et al, 2015), and concussion (Pasternak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Standard neuroimaging techniques do not provide quantifiable data on brain microstructural architecture, however this study has demonstrated a reproducible and reliable method for obtaining whole brain maps with quantifiable estimates of brain microstructure. This measure is stable enough to be used in longitudinal studies lasting at least up to three months; and provides information on a voxel-or region-wise basis for analysis of subcortical structures, lesions, or developing brains (Dhollander et al, 2017;Mito et al, 2018;Mito et al, 2019;Bastiani et al, 2019). Related microstructural analysis of free water signal fractions has been performed in the context of Parkinson's disease (Ofori et al, 2015;Burciu et al, 2016), Schizophrenia (Pasternak et al, 2012;Mandl et al, 2015), and concussion (Pasternak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pietsch et al, (2019) applied two different WM response functions representing mature and immature WM in a developing adolescent cohort to observe WM maturation. Mito et al, (2019) proposed to apply a statistical framework of compositional data analysis to analyze the full 3-tissue composition of WM-, GM-and CSF-like signal fractions directly to study microstructure in white matter lesions, following the initial suggestion of moving towards such WM/GM/CSF-like diffusion signal fraction interpretation by Dhollander et al (2017). In Aerts et al, (2019), this idea was furthermore used for the purpose of disentangling WM FODs representing infiltrated WM tracts in the presence of gliomas, so as to enable more reliable within-tumor tractography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations